2006
DOI: 10.1096/fj.05-4022com
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to ATP via alteration of P2X receptor function in dystrophic mdx mouse muscle cells

Abstract: Pathological cellular hallmarks of Duchenne muscular dystrophy (DMD) include, among others, abnormal calcium homeostasis. Changes in the expression of specific receptors for extracellular ATP in dystrophic muscle have been recently documented: here, we demonstrate that at the earliest, myoblast stage of developing dystrophic muscle a purinergic dystrophic phenotype arises. In myoblasts of a dystrophin-negative muscle cell line established from the mdx mouse model of DMD but not in normal myoblasts, exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 64 publications
9
85
0
1
Order By: Relevance
“…P2X7 receptors are widely distributed in immunocompetent cells of the central and peripheral nervous system, including SC, and the pathogenetic role of P2X7 and the therapeutic potential of P2X7 antagonists are being increasingly recognized in several neurological disorders, including peripheral neuropathies (32,36,51). It is also noteworthy that overexpression of P2X7 and the consequent increase of Ca 2ϩ influx have been implicated in the pathogenesis of Duchenne muscular dystrophy (52).…”
Section: Discussionmentioning
confidence: 99%
“…P2X7 receptors are widely distributed in immunocompetent cells of the central and peripheral nervous system, including SC, and the pathogenetic role of P2X7 and the therapeutic potential of P2X7 antagonists are being increasingly recognized in several neurological disorders, including peripheral neuropathies (32,36,51). It is also noteworthy that overexpression of P2X7 and the consequent increase of Ca 2ϩ influx have been implicated in the pathogenesis of Duchenne muscular dystrophy (52).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on our current and previous studies showing that neither the P2X 7 R agonist BzATP (this study) nor its antagonist KN-62 (Scemes et al, 2003) had an impact on progenitor cell migration. Although the P2X 7 receptors have been proposed to be a component of the inflammatory response in astrocytes (Narcisse et al, 2005), and a contributor to pathogenic Ca 2+ entry (Yeung et al, 2006), and cell death (Zhang et al, 2005;Wang et al, 2004), further studies are needed to disclose the impact of these ionotropic receptors on neural progenitor cell (patho) physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the involvement of purinergic signalling in muscle regeneration may lead to novel therapeutic strategies for the treatment of muscle disease. Immortalized myoblast cell lines derived from the mdx mouse (SC5) and control (dystrophin positive) myoblasts (IMO) from the same parent mouse strain have been used to investigate changes in P2X receptor expression and function in dystrophic muscle [355]. It was shown that a purinergic dystrophic phenotype arises at the earliest myoblast stage of developing dystrophic muscle.…”
Section: Muscular Dystrophymentioning
confidence: 99%